Management of primary ciliary dyskinesia in European children: recommendations and clinical practice - KARADAĞ, BÜLENT TANER (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2012)
The European Respiratory Society Task Force on primary ciliary dyskinesia (PCD) in children recently published recommendations for diagnosis and management. This paper compares these recommendations with current clinical practice in Europe. Questionnaires were returned by 194 paediatric respiratory centres caring for PCD patients in 26 countries. In most countries, PCD care was not centralised, with a median (interquartile range) of 4 (2-9) patients treated per centre. Overall, 90% of centres had access to nasal or bronchial mucosa! biopsy. Samples were analysed by electron microscopy (77%) and ciliary function tests (57%). Nasal nitric oxide was used for screening in 46% of centres and saccharine tests in 36%. Treatment approaches varied widely, both within and between countries. European region, size of centre and the country's general government expenditure on health partly defined availability of advanced diagnostic tests and choice of treatments. In conclusion, we found substantial heterogeneity in management of PCD within and between countries, and poor concordance with current recommendations. This demonstrates how essential it is to standardise management and decrease inequality between countries. Our results also demonstrate the urgent need for research: to simplify PCD diagnosis, to understand the natural history and to test the effectiveness of interventions.
Keywords: Bronchiectasis; ciliary motility disorders; diagnosis; Kartagener syndrome; primary ciliary dyskinesia; therapy; DIAGNOSIS; STATE